Evaluating the Effectiveness of the Step-By-Step Guide Module in Enhancing Working Drawing Mastery Among Architecture Students - Suib, Rafidah bt; Yusop, Norzalina bt Md; Mohtaram, Siti Amirah (Tropical Scientific Journal, 2026)
Objective: This research aims to analyze the effectiveness of a step-by-step learning module in improving the mastery of working drawings among Semester 2 Diploma in Architecture students for the course DCA20333: Working Drawing 1. The primary focus of the study is to evaluate the extent to which this module assists students in mastering the transition between manual drawing skills and CADD applications, which form the core of the course assessment. A common problem faced by students at this stage is confusion in understanding technical symbolism, annotation standards, and the logic of drawing arrangement that complies with industry practices. Research Method: This study utilizes a survey method involving the distribution of questionnaires to obtain student feedback on the effectiveness of the module regarding their assessment achievement Findings: The results are expected to show that the systematic use of the module significantly enhances technical understanding and accelerates the process of completing quality drawings. Originality: The research findings will serve as a solid foundation to support the publication of the book Step-By-Step Guide: Working Drawing 1 as a primary reference material for the DCA20333 course, thereby bridging the gap between academic theory and practical requirements in the field of architecture.